HEALTH RISK ASSESSMENT OF SOME HEAVY METALS IN SOIL SAMPLES AROUND IDENTIFIED METAL WORKSHOPS - Abdullahi, S.; Musa, M. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Soil properties may change due to climate change, but in recent times, the changes occur as a result of anthropogenic activities such as metal workshop operations. This study was conducted to assess the impact of metal contamination on human health due operating activities of metal workshops. In this research work which was carried out to estimated human health risk due to heavy metal contamination around metal workshops, five different workshops, Garejin Oga Abdul (GOA), Nakowa Welding Construction (NWC), Garejin Da’awa (GDH), Garejin Adamu Salisu (GAS) and Garejin Iliya Maina (GIM) all in Potiskum town, Yobe State were sampled for the study and analyzed for eight heavy metals (Pb, Zn, Cr, Cd, Co, Mn, Ni and Cu) levels using Atomic Absorption Spectrophotometer (AAS). Results from this study revealed that Cr (2.37E-01) and Co (5.77E-04) recorded the highest and lowest hazard quotient and the trend of total hazard quotient of all the heavy metals analyzed is Cr > Pb > Mn > Cu > Cd > Ni > Zn > Co. The hazard Quotients (HQ) and Hazard Index (HI) deduced from the workshops fall below the acceptable level indicating unlikelihood of non-carcinogenic health risks. However, GDH, GIM and GOA workshops were estimated to pose medium cancer risks with Incremental Lifetime Cancer Risk (ILCR) values of 8.195 x 10-5, 6.313 x 10-5 and 7.443 x 10-5 respectively.